Samparka : Sureśa Dalāla mūlyaṅkanagrantha - Bhāyāṇī, Utpala; Dalal, Suresh Parshottamdas, 1932- (Sureśa Dalāla Sanmāna Samiti, 1982)
Festschrift honoring Suresh Parshottamdas Dalal, b. 1932, Gujarati litterateur; comprises articles on his life and works.